Peran Pengungkapan Sustainability Report dan Kepemilikan Institusional dalam Meningkatkan Nilai Perusahaan - Maghfiratul Aini; Erna Chotidjah Suhatmi; Umi Hanifah (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
The purpose of this research is to determine whether and how sustainability reports and institutional ownership affect company value. This study used a quantitative approach that relied on purposive sampling. Annual financial reports, sustainability reports, and stock price data were used as sources of secondary data for this study. The companies listed on the Indonesia Stock Exchange in the basic industries and chemicals sectors from 2021 to 2024 were considered. In order to analyse the research outcomes, SPSS was used in conjunction with multiple linear regression.. According to the findings, institutional ownership significantly affects firm value, whereas sustainability report disclosure has little impact. Sustainability disclosure in this industry is still mostly about checking boxes and hasn’t turned into a meaningful signal for investors, according to this study. On the other hand, institutional ownership helps keep agencies from competing interests. With implications for corporate disclosure strategies and investor decision-making, this study offers empirical insights into the unique roles of ownership systems and disclosure mechanisms in predicting business value.